In the Name of Women. Comparing Gynecologists’ Discourses About Abortion in Italy - Ghigi, Rossella; Quaglia, Valeria (Italian Sociological Review, 2023)
For at least fifty years, voluntary termination of pregnancy has represented a terrain of struggles among different theoretical and political positions, often claimed ‘in the name of women’ (Pitch, 1992; Koralewska & Zielińska, 2022). The rate of objecting doctors and recent changes in the regulation of the pharmacological abortion have rekindled the debate on the actual access to the service in Italy. And, once again, the different parties refer to ‘women’s interests and well-being’, sometimes explicitly in the name of a feminist position, sometimes in the name of human rights, sometimes on scientific evidence. Drawing on a field research based on in-depth interviews conducted with gynecologists and other specialists, this article explores the discourses around the legitimacy, the best techniques, and the most appropriate conditions of abortion to understand how these health professionals set their own ‘threshold of legitimacy’. As we shall see, the need to reduce their own dissonance and value conflicts lead them to set a hierarchy of deservingness of abortion that put women’s behavior into a moral ranking. Again, very different positions are rhetorically taken in the name of women, whose actual agency is discussed at the light of our research results.